Characterization of leukemogenic virus produced by a new line of Friend erythroleukemia virus-transformed cells. - Friend, C (1984)
A new cell line designated SQ-A was established from the spleen of a leukemic DBA/2J mouse inoculated with the anemic strain of Friend erythroleukemia virus (FLV-A). The cells are similar in morphology, growth pattern, and tumorigenicity to our prototype erythroleukemia line 5-86 but are more sensitive to the cytotoxic effects of inducers of differentiation. The virus produced by SQ-A cells induces erythroleukemia associated with anemia in adult mice but has little activity when assayed on XC cells. It was characterized to determine what factors influence its leukemogenic potential. As compared to the attenuated virus from cultures of 5-86 and G-2 cells, the subunits of the RNA from the virions of SQ-A cells are the same size, and the amount of reverse transcriptase activity and RNase H present in the purified virions of the three lines are similar. However, differences are observed in levels of endonuclease and protein kinase. Both enzymes are increased in SQ-A virions. The activity of protein kinase in SQ-A virions is about 5 times higher than that in the attenuated virions. The number of polypeptides and their phosphorylation patterns also distinguish the virions of SQ-A. Whereas 5-86 virions contain seven proteins, three of which are phosphorylated in vitro, SQ-A virions contain eight proteins, all of which are phosphorylated. The extra protein in SQ-A virions has a molecular weight of 25,000 and is not glycosylated.